2,6-Diamino-4-chloropyrimidinium 4-carboxybutanoate - Edison, Bellarmin; Balasubramani, Kasthuri; Thanigaimani, Kaliyaperumal; Khalib, Nuridayanti Che; Arshad, Suhana; Razak, Ibrahim Abdul (International Union of Crystallography, 2014)
In the title molecular salt, C4H6ClN4+.C5H7O4 -, the cation is essentially planar, with a maximum deviation of 0.037 (1) A ° for all non-H atoms. The anions are self-assembled through O—H...O hydrogen bonds, forming a supramolecular zigzag chain with graph-set notation C(8). In the crystal, the protonated N atom and the 2-amino group of the cation are hydrogen bonded to the carboxylate O atoms of the anion via a pair of N—H...O hydrogen bonds with an R2 2(8) ring motif. This motif further self-organizes through N—H...O and O—H...O hydrogen bonds, generating an array of six hydrogen bonds, the rings having graph-set notation R3 2(8), R2 2(8), R4 2(8), R2 2(8) and R3 2(8). In addition, another type of R2 2(8) motif is formed by inversion-related pyrimidinium cations via N—H...N hydrogen bonds, forming a two-dimensional network parallel to (101).